Obstacles to the use of educational techniques in the development of different skills in children with autism disorder from the perspective of special education teachers in the Kingdom of Saudi Arabia - Zahra, Nasreen Abd El- Elah; Ali, Amal Mahmoud (Journal of Educational and Psychological Sciences, 2019)
The present study aimed at revealing the reality of the use of educational techniques by teachers of children with autism disorder and the obstacles that prevent their use. The analytical descriptive method was applied to 25 teachers of autism children at the Center for Autism Disorder/، And the questionnaire was used as a tool for study and included 17 words.The results showed that the most obstacles facing the use of educational techniques in the education of children with autism disorder by teachers is the lack of classrooms for the use of educational techniques، and the lack of budget availability of educational technology، and the need of more than one teacher to use the technology of education at the same time but not available، In addition to the fact that the price prevents the acquisition، and the weakness of the possibility of compensation damage or loss، where the averages of the terms of these terms between (1.80- 2.00) and percentages between (80%- 100%)، In light of the results، the study recommended the need to provide special rooms in the centers of autism to use the educational techniques and to provide the needs of teachers of teaching techniques to develop a budget for these special techniques، and the need for a specialist in educational technology as well as teachers to maintain devices constantly and increase the desire of teachers to use.
Keywords: Obstacles; use; educational techniques; autism; special education teachers